Energy-saving Operation Optimization Strategy of Urban Rail Transit Co-phase Energy Storage Power Supply System - HOU Feng; WANG Shuai; SUN Zhongrui (Chengshi guidao jiaotong yanjiu, 2024)
Objective As modular co-phase power supply devices are used in Guangzhou Metro Line 18,it is necessary to study the energy-saving operation optimization strategy of the co-phase energy storage power supply system in order to solve the problem of low utilization rate of regenerative braking energy in the co-phase traction power supply system. Method With the goal of minimizing the daily electricity cost of traction substation to balance the node power,and constrained by operation characteristics of power supply devices and energy storage devices, an optimized energy-saving model of co-phase energy storage power supply system is established. Based on the measured load process data of a traction substation on Guangzhou Metro Line 18, the traction load process of urban rail transit is analyzed. CPLEX commercial planning solver is used to solve the above model and finally the optimal energy management scheme of the co-phase energy storage system is obtained. Result & Conclusion The energy storage power supply system with the supercapacitor connected to DC link of the modular co-phase power supply device works as follows: with the peak cutting and valley filling effect of the supercapacitor on the traction load, the regenerative braking energy utilization rate of the traction power supply system can be increased, saving the electricity cost of urban rail transit operators consequently. The test results show that compared with the traditional co-phase power supply system, the co-phase energy storage power supply system with supercapacitor can increase the regenerative braking energy utilization rate to 92.88%, and reduce the daily electricity cost by 9.65%, showing remarkable energy saving effect. increase the regenerative braking energy utilization rate to 92.88%.